Το θέατρο : κύκλος διαλέξεων (Δίφρος, 1960)
Ομιλητές: 'γγελος Τερζάκης -- Πέτρος Χάρης -- Γεωργ. Κουρνούτος -- Τάκης Μουζενίδης -- Γιώργος Βακαλό -- Πέτρος Κατσέλης -- Μάριος Πλωρίτης -- Δημήτρης Μυράτ -- Κούλα Πράτσικα -- Μαρία Αμαριώτου